A disputa na construção política dos direitos humanos no Brasil: as pautas expressas no I Fórum Mundial de Direitos Humanos (2013) - Valdivia, Antonia Marcia Araujo Guerra Urquizo (2017)
This research brings the analysis of the dispute in the construction of human rights in Brazil from the reasons that led the president Dilma Rousseff to hold the First World Forum of Human Rights (WFDH) in 2013, as an attempt and a political response, through the correlations of forces established in the field of human rights, which made it possible for the government to take a political breath, especially in relation to the conservative groups they intended for non-implementation of the PNDH-3. In addition, the government achieved a new renegotiation with the social, dissatisfied, due to the non-performance of the actions established in the PNDH-3. The analysis that underlies this thesis is based on the core of historical and dialectical materialism, starting from the relationship of social classes, demanded by the social direction of concrete political action, on a tense terrain that forms the human rights. To do so, it is based on three dimensions of human rights: civil and political rights, economic, social and cultural rights, and the rights of solidarity or fraternity (diffuse and collective). The option was for the methodology of qualitative social research, which combined bibliographical research, documentary research and field research (interviews) with the subjects that work in the scope of human rights and collaborators in the construction of the I FMDH. The results of the research reveal that Brazil advanced in the political-juridical modernization after the Federal Constitution of 1988, but they also point out that conservatism is maintained, based on the strong cultural heritage of Brazil colony, fueling the dispute of political projects in an offensive conjuncture Neoliberal